Database and expert systems applications. 26th International Conference, DEXA 2015, Valencia, Spain, September 1-4, 2015, Proceedings /: 26th International Conference, DEXA 2015, Valencia, Spain, September 1-4, 2015, Proceedings. Part I : (2015) - Unknown
No abstract available